The prevalence of cardiorenal anemia syndrome among patients with heart failure and its association with all-cause hospitalizations: a retrospective single-center study from the Middle East - Manla, Yosef; Kholoki, Obada; Bader, Feras; Kanwar, Oshin; Abidi, Emna; El Nekidy, Wasim S.; Hijazi, Fadi; Attallah, Nizar (Frontiers in Cardiovascular Medicine, 2023)
Background and aim Little is known about the burden of cardiorenal syndrome (CRS) and cardiorenal anemia syndrome (CRAS) in the Middle East Region. Furthermore, whether the occurrence rates of CRAS differ across heart failure (HF) phenotypes is not widely investigated. We aimed to examine the prevalence of CRS and CRAS in patients with HF, compare characteristics of patients with CRAS-HFrEF vs. CRAS-HFpEF, and investigate anemia association with 1-year all-cause hospitalizations. Methods HF patients who visited a multidisciplinary HF clinic at a single center between 10-2015 and 06-2022 (n = 968) were retrospectively included. Differences in rates of CRAS prevalence, and patients’ characteristics of those with CRAS-HFrEF vs. CRAS-HFpEF were determined using appropriate testing methods. Generalized estimating equation (GEE) models were used to determine if anemia was associated with higher rates of hospitalization. Results CRS was prevalent in 34.4% of subjects, while 25.3% had CRAS. CRAS prevalence rates among patients with HFpEF vs. HFrEF were comparable (27.2% vs. 24.2%, p = 0.3). Compared to patients with HFrEF-CRAS, those with HFpEF-CRAS were more likely females (p < 0.001), had a higher burden of hypertension (p = 0.01), and lower hemoglobin (p = 0.02). In an adjusted GEE model, anemia was associated with an average increase of 1.8 admissions in CRS patients (p = 0.015). Conclusion In patients with HF, 1 in 3 patients presented with CRS, and 1 in 4 patients had CRAS. The prevalence of CRAS was comparable among those HFpEF and HFrEF. Anemia was associated with an increased rate of 1-year all-cause hospitalization in CRS patients.